Relationship Between Central Obesity and The Risk of Hypertension in Obesity Adolescents - Ardina Maharani, Putri; Widjaja, Nur Aisiyah; Ardiana, Meity; Hanindita, Meta Herdiana (Pelopor Publikasi Akademika, 2023)
The increasing prevalence of central obesity in adolescents is accompanied by an increase in risk factors for cardiovascular disease. The study aims to analyze the relationship between central obesity and the risk of hypertension in obese adolescents, including both male and female subjects. This study was undertaken to provide opportunities for further exploration of the relationship between central obesity and hypertension in adolescents. The study was a retrospective observational study that utilized medical record data from a previous research project entitled